Pemanfaatan Social Media oleh Praktisi Public Relations di Yogyakarta - Hanindyalaila Pienrasmi (Program Studi Ilmu Komunikasi, 2015)
Social media has changes the way public relations practitioners in doing their jobs related to communicate with the public how to communicate both individually and at the corporate level. Social media become a challenge for practitioners to improve their technical and managerial abilities as a professional to deak with the development of new technology. Practitioners continue to know more about social media in order to optimize utilization and help the company to establish a better relationship with the publics.Based on in-depth interviews with public relations practitioners in Yogyakarta, it was found that practitioners are already utilizing social media in supporting the activities of public relations communication functions in the company. In this research whole practitioners has been used social media for branding activities and dissemination of information about company's marketing. In addition, most practitioners have also been utilizing social media as a medium to communicate with the publics in a two-way conversation and began to engage in it. Some of the practitioners also began to involve social media in monitoring issues and crisis communication and dissemination of information about the activities of corporate social responsibility and social campaigns that is undertaken by the company.